Republication of “Ankle Fracture-Dislocations: A Review” - Kevin A. Lawson MD; Alfonso E. Ayala BS; Matthew L. Morin MD; L. Daniel Latt MD, PhD; Jason R. Wild MD (Foot & Ankle Orthopaedics, 2023)
Ankle fractures are common musculoskeletal injuries that may result in tibiotalar joint dislocations. Ankle fracture-dislocations occur via similar mechanisms as ankle fractures, although the persistence or magnitude of the deforming force is sufficient to disrupt any remaining bony or soft-tissue stability. Ankle fracture-dislocations likely represent distinct clinical entities, as the pathology, management, and patient outcomes following these injuries differ from those seen in more common ankle fractures without dislocation. Ankle fracture-dislocations have higher rates of concomitant injury including open fractures, chondral lesions, and intra-articular loose bodies. Long-term outcomes in ankle fracture-dislocations are worse than ankle fractures without dislocation. Higher rates of posttraumatic osteoarthritis and chronic pain have also been reported. In this review, we discuss the current literature regarding the history, management, and outcomes of ankle-fracture dislocations and highlight the need for future study.